Spatial and temporal dynamics of predator-prey species interactions off western Canada. (12th May 2017) - Fu, Caihong; Olsen, Norm; Taylor, Nathan; Grüss, Arnaud; Batten, Sonia; Liu, Huizhu; Verley, Philippe; Shin, Yunne-Jai
Abstract: Ecosystem models are valuable tools for informing fisheries management due to their ability to simulate the spatial dynamics of modelled species, their trophic interactions, and their responses to fishing in an ecosystem context. In this study, we developed an OSMOSE (Object-oriented Simulator of Marine Ecosystems Exploitation) model for the Pacific North Coast Integrated Management Area (PNCIMA) ecosystem off western Canada, which simulated the entire life cycle of six key species and for the first time integrated spatial population structure and "background" taxa. Background taxa are of secondary importance for the study at hand but have the potential to be important prey or predators of the key species. The primary aim of the study was to explore how the population dynamics of the key species differed over time and different management areas, with results focusing on Pacific Herring ( Clupea pallasii ) and Pacific Cod ( Gadus macrocephalus ) that have been assessed on a single-species basis in the last 5 years. Results found that the population dynamics of a specific species varied in different management areas due to differences in species interactions particularly in the form of predation mortality, which supports the current area-specific assessment and management framework. The study also indicated that increasing predation mortality may have caused the decline of the Pacific Cod populations. By contrast, increasing starvation mortality was found to be a limiting factor for the Pacific Herring populations. The discoveries from these OSMOSE simulations provide important information for fisheries management within the PNCIMA ecosystem.